The effect of acupuncture on pain and swelling of arthritis animal models: A systematic review and meta-analysis - Yu, Wei-Lien; Kim, Seung-Nam (Frontiers in Genetics, 2023)
Arthritis, the inflammation of joints, attributes to the patient’s pain, joint deformation, and limited range of motion. Emerging studies have shown the effects of acupuncture on different types of arthritis. We aimed to assess the effects of acupuncture on arthritis animal models and summarize the related mechanisms. We retrieved studies that met our criteria from PubMed, MEDLINE, EMBASE and the Research Information Service System. The quality assessment was evaluated by using the Systematic Review Centre for Laboratory Animal Experimentation’s risk of bias tool. The pain withdrawal latency, pain withdrawal threshold, and paw volume data were digitized using Engauge Digitizer software. The meta-analysis was performed, and the figures were generated using RevMan software. The meta-analysis of data from 21 animal studies revealed that acupuncture increased tolerance to pain stimuli, and reduced swelling in arthritis animals. Although the number of included studies is insufficient, the results suggest acupuncture to be effective in improving arthritis-induced inflammation and pain by regulating the nervous and immune system.